Utilization of de-oiled rice bran as a feedstock for renewable biomethane production. (September 2020) - Jha, Bhaskar; Chandra, Ram; Vijay, Virendra K.; Subbarao, Paruchuri M.V.; Isha, Adya
Abstract: This research aims to study biogas production using de-oiled rice bran as a renewable source of energy. The measured volatile solids content of de-oiled rice bran revealed its significant potential for biogas production. In the first phase of the experimentation, the hydrolytic behavior was studied to determine the optimal total solids (TS) concentration of the substrate, required for maintaining the favourable environmental condition for efficient anaerobic digestion. Out of four TS concentration taken (5%, 7.5%, 10%, and 15%), the most significant result was found for the substrate maintained at 5% TS. As per the finding of the hydrolysis experiment, further investigation was conducted using 60 L plastic made digester under continuous feed mode and at mesophilic temperature condition in three replicates. The results revealed average specific biogas yield of 0.470 L/g TS and 0.547 L/g VS with an average specific methane production yield of 0.232 L/g TS and 0.270 L/g VS. The most encouraging finding of this study was the high material conversion efficiency (maximum 67.54%), which makes de-oiled rice bran more potential feedstock than other conventional biomass. The novelty of the present study lies in the development of efficient 'secondary inoculum' through a continuous system. The inoculum developed through continuous mode gives a higher degree of control than batch mode. Along with the microbial growth, the secondary metabolites produced during the anaerobic digestion process, (which plays a crucial role in process continuation) can also be sustained simultaneously in the developed continuous system. Highlights: Anaerobic digestion of de-oiled rice bran has been explored in depth. Digester maintained at 5.0% TS concentration showed best result. Average specific methane production yield of 0.232 L/g TS and 0.270 L/g VS has been found. Average volatile solid removal efficiency of 52.3% was recorded.